2004
DOI: 10.1021/ja038968t
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Studies of the Ethylene Trimerization Reaction with Chromium−Diphosphine Catalysts:  Experimental Evidence for a Mechanism Involving Metallacyclic Intermediates

Abstract: The oligomerization of ethylene typically leads to a broad range of R-olefins; catalytic systems that are selective for specific desirable alkenes would be of great interest. There have been several recent reports of trimerization of ethylene to 1-hexene with high selectivity. 1 While some ethylene trimerization catalysts are based on titanium and tantalum, 1j,k chromium-based systems generally display higher activity, selectivity, and thermal stability. 1b-i A recent communication describes a catalyst, genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
256
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 294 publications
(272 citation statements)
references
References 16 publications
11
256
1
3
Order By: Relevance
“…[8] Furthermore, the authors were able to shed light on the formation of the cyclic C 6 side products, methylenecyclopentane and methylcyclopentane, which are formed in a 1:1 ratio by means of a disproportionation pathway. Their findings are in good agreement with observations made by Bercaw et al on the selective chromium-catalysed trimerisation of ethylene [9] and Gibson et al for the oligomerisation of ethylene by chromium catalysis according to a Schulz-Flory type of distribution. [10] In all these research activities, carried out by established groups in the field of ethylene oligomerisation, a metallacycle mechanism was proven for the selective, Cr-catalysed ethylene oligomerisation.…”
Section: Introductionsupporting
confidence: 92%
“…[8] Furthermore, the authors were able to shed light on the formation of the cyclic C 6 side products, methylenecyclopentane and methylcyclopentane, which are formed in a 1:1 ratio by means of a disproportionation pathway. Their findings are in good agreement with observations made by Bercaw et al on the selective chromium-catalysed trimerisation of ethylene [9] and Gibson et al for the oligomerisation of ethylene by chromium catalysis according to a Schulz-Flory type of distribution. [10] In all these research activities, carried out by established groups in the field of ethylene oligomerisation, a metallacycle mechanism was proven for the selective, Cr-catalysed ethylene oligomerisation.…”
Section: Introductionsupporting
confidence: 92%
“…In recent years, Bercaw and co-workers have shown that, by analyzing the isotopologue distributions obtained in a C 2 H 4 /C 2 D 4 co-trimerization reaction, the absence of H/D scrambling implies a metallacyclic mechanism for this reaction. 23,24 Similar observations have been made for ethylene tetramerisation reactions. 25 We were interested to find out whether this technique can also be applied to higher oligomers and polymers and we have therefore carried out Chromium catalysts 1 and 2 shown in Scheme 2 and related systems have been shown previously to be highly active for the oligomerization of ethylene.…”
Section: Introductionsupporting
confidence: 77%
“…One possibility is the oxidative cyclization of two ethylene molecules to form a chromacyclopentane species (43)(44)(45), whereas the other is a direct oxidative C-H bond activation to form a Cr-vinyl hydride, both of which are proposed initiation steps for the Phillips catalyst (13,14,46,47). In both cases, we were unable to locate stable minima.…”
Section: Significancementioning
confidence: 88%